Connected and Integrated Questions in Teaching Reading Vietnamese Poems in the Medieval Period for High School Students - Hien, Pham Thi Thu; Hang, Ha Thanh (VNU Journal of Science: Education Research; Vol 36 No 2, 2020)
Vietnamese poems in the Medieval period have been taught in high schools for a long time. However, many students find difficult to read/receive these works because they have been around for a long time and have unique characteristics. At the same time, the teacher's reading comprehension method also does not help students to link the reading content from the text to their current life. The paper proposes a way to overcome the aforementioned limitation, which is to build and use connected and integrated questions in teaching reading comprehension of Vietnamese poems in the Medieval period for high school students, in order to connect activities teaching and learning these works with real life and develop some general competencies as well as specific competencies for learners.